Pilates − A Teachers’ Manual Exercises with Mats and Equipment for Prevention and Rehabilitation - Geweniger, Verena. (Springer Berlin Heidelberg : Imprint: Springer, 2014)
Pilates For Prevention And Therapy Millions of people use Pilates training to improve health and fitness, or regain movement capability following injury or disease. Competent, professional support from physiotherapists, sports teachers and trainers is of vital importance for every client or patient. "Pilates: A teachers’ manual“ provides you, as a professional, with fundamental teaching structures and practical guidelines. The concepts which characterized  the traditional approach to Pilates are combined with the evolved methods of modern Pilates training, and backed up by current findings in sports science and kinesiology. Pilates For Prevention - Methodology - movement categories, functional systems, functional anatomy and biomechanics, etc. - Techniques for testing and classification of training objectives - Modern mat training: ca. 40 exercises - Class plans tailored to specific groups (beginner, intermediate, advanced, pre-natal, etc.) Pilates For Therapy - Basics - ICF classification, phases of rehabilitation, strength, mobility - Exercises utilizing the Pilates equipment (Reformer, Cadillac, etc., small apparatus) - Therapeutic mat exercises - Movement in muscle chains -Treatment examples from orthopedics, neurology, etc. Clear descriptions - All exercises clearly presented on double pages - Concise movement instructions -  More than 500 color photographs illustrate movements step-by-step - References and practical tips on all themes Inter-disciplinary relevance and comprehensibility - With glossary and clarification of anatomical terms The first English edition of the successful German work.